Three new caddisflies species of the fossil genus Archaeotinodes (Insecta: Trichoptera: Ecnomidae) from the Baltic Amber - Melnitsky, Stanislav I.; Ivanov, Vladimir D. (Zootaxa, 2013)
Three new caddisflies species of the fossil genus Archaeotinodes: Archaeotinodes petropolitana sp. nov., Archaeotinodes regiomontana sp. nov., and Archaeotinodes rossica sp. nov. from the Baltic amber (Upper Eocene, 40 million years old), are described and illustrated.